2006
DOI: 10.1080/13697130600655852
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for hormone replacement therapy of Asian women during the menopausal transition and thereafter

Abstract: These Guidelines summarize the position of an Expert Panel on Menopause in Asian Women regarding the use of hormone replacement therapy (HRT) during the menopausal transition and thereafter. They are intended to aid gynecologists, family physicians and other health-care professionals in providing optimal care to menopausal Asian women who desire HRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The study also revealed that there was lack of knowledge amongst the general public regarding the menopause and its health consequences [10]. Since then, public health activities on promotion of women's health were launched and guidelines have been issued on the prescription of HRT for Asian women as there is evidence that menopausal symptoms may vary considerably when comparing Asian women with their western counterparts [11]. These actions may have helped to increase the health awareness of postmenopausal women and the usage of HRT in Hong Kong.…”
Section: Discussionmentioning
confidence: 98%
“…The study also revealed that there was lack of knowledge amongst the general public regarding the menopause and its health consequences [10]. Since then, public health activities on promotion of women's health were launched and guidelines have been issued on the prescription of HRT for Asian women as there is evidence that menopausal symptoms may vary considerably when comparing Asian women with their western counterparts [11]. These actions may have helped to increase the health awareness of postmenopausal women and the usage of HRT in Hong Kong.…”
Section: Discussionmentioning
confidence: 98%
“…However, interestingly while HT is readily available to Hispanic women living in the United States, Hispanic women are least likely to use HT to treat their menopausal symptoms, opting for more natural methods such as herbs, diet, vitamins and exercise 13. In Costa Rica, the average age at onset of menopause is 50.6 years, and Costa Rican women experience menopausal symptoms comparable to their counterparts in the United States 13,14. Similar to Hispanic women living in the United States, most Costa Rican women do not often use HT to treat menopausal symptoms, but instead opt for specific herbal medicines 13,14.…”
Section: Introductionmentioning
confidence: 99%
“…In Costa Rica, the average age at onset of menopause is 50.6 years, and Costa Rican women experience menopausal symptoms comparable to their counterparts in the United States 13,14. Similar to Hispanic women living in the United States, most Costa Rican women do not often use HT to treat menopausal symptoms, but instead opt for specific herbal medicines 13,14. While there are some limited ethnobotanical data are available for these specific herbal therapies used by Costa Rican women, many of these plant species have never been scientifically investigated for their potential use for the management of menopausal symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, an expert panel was created in 2005 for the discussion and creation of guidelines for hormone replacement therapy (HRT) of Asian women during the menopause transition and thereafter. 6 APMF conducted a consensus meeting with participation of representatives from all 14 countries on April 10 to 13, 2008, at Ho Chi Minh City, Vietnam. The group agreed on the APMF Consensus Statement on Management of Menopause, which has been published on the Web site of the APMF.…”
mentioning
confidence: 99%